VD_FINDINFO HC / 2018 / 513 vom 28. Mai 2018 - VD Tribunal cantonal (2018)
BAIL À LOYER, RÉSILIATION ANTICIPÉE, RÉSILIATION IMMÉDIATE, EXPULSION DE LOCATAIRE | 257d CO, 271 al. 1 CO, 273 al. 1 CO, 248 let. b CPC (CH)